Inclusion versus privilege: motivations for loyalty to social orders - Ekadumov, Andrew (Journal of the Belarusian State University. Philosophy and Psychology, 2022)
Loyalty to pre-modern and anti-modern sociocultural strategies is motivated by the demand for exclusive opportunities, legal and moral irresponsibility, which cannot be satisfied by the institutions of mature modernity. Loyalty to the modern social order guaranteeing inclusion is motivated by the actors’ desire for guaranteed equality of opportunities. However, the inclusive social order creates legal obstacles and moral problems in the realisation of claims to exclusive rights and moral irresponsibility. The motivational advantages of an inclusive social order are its weaknesses amid the aspiration for freedom from legal responsibility and moral obligations. The high economic efficiency and high level of protection from violence guaranteed by the social institutions of mature modernity, however, are inconsistent with legally sanctioned and ethically acceptable practices of segregation. The actors’ need for both high moral self-esteem and legal and moral irresponsibility to benefit from unequal opportunities initiates loyalty to pre-modern or quasi-traditional practices and notions that sanction segregation.